2021
DOI: 10.1177/1532673x211041319
|View full text |Cite
|
Sign up to set email alerts
|

We Have It Totally Under Control? Exploring the Effects of Ideology and Knowing Someone Diagnosed With COVID-19 on Evaluations of President Trump’s Leadership on the Pandemic

Abstract: President Donald Trump has made various decisions, many controversial, to manage the coronavirus pandemic. The reaction to President Trump’s leadership has been met with a mixed response from the public. This raises an important question; what factors influence a citizen’s evaluation of President Trump’s response to the pandemic? We develop a theory that links a citizen knowing someone diagnosed with COVID-19 with their evaluation of President Trump’s management of the pandemic, with the expectation that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
1
Order By: Relevance
“…When controlling for the strictness of lockdown policies a study by Giommoni and Loumeau (2020) revealed that in French municipal elections, the voter turnout and support for the incumbents were higher in localities with stricter lockdown policies. This was in contrast with other studies, such as the one of Byers and Shay (2022) which proves that knowing someone who has been diagnosed with COVID-19 reduces the impact of ideology on a citizen's assessment of political leadership. Other recent empirical studies also assessed the COVID-19 effect on electoral participation emphasising that the rate of citizens exercising their right to vote decreased.…”
Section: Literature Reviewcontrasting
confidence: 92%
“…When controlling for the strictness of lockdown policies a study by Giommoni and Loumeau (2020) revealed that in French municipal elections, the voter turnout and support for the incumbents were higher in localities with stricter lockdown policies. This was in contrast with other studies, such as the one of Byers and Shay (2022) which proves that knowing someone who has been diagnosed with COVID-19 reduces the impact of ideology on a citizen's assessment of political leadership. Other recent empirical studies also assessed the COVID-19 effect on electoral participation emphasising that the rate of citizens exercising their right to vote decreased.…”
Section: Literature Reviewcontrasting
confidence: 92%
“…Some journals, such as The Leadership Quarterly (Eagly & Heilman, 2016), American Psychologist (Chin, 2010), Education Sciences (O'Connor, 2018), and Leadership (Wilson, 2020), focus on issues of gender and leadership effectiveness. Several other journals like the Journal of Leadership and Organizational Studies (Moss et al, 2022), American Politics Research (Byers & Shay, 2021), Journal of European Public Policy (Waylen, 2021), Politics and Gender (Johnson & Williams, 2020), Leadership (Wilson, 2020), SN Comprehensive Clinical Medicine (Bwire, 2020), and Journal of Applied Psychology (Sergent & Stajkovic, 2020) address the reluctance of masculine leaders to take Covid-19 seriously and implement mitigation measures to gain public trust.…”
Section: Introductionmentioning
confidence: 99%